WORD WALL WITH DESIGN THINKING AND LOCAL WISDOM TO ENHANCE CRITICAL THINKING - Nova Viona Elfani; Ari Metalin Ika Puspita; Raden Roro Nanik Setyowati; Neni Mariana; Nurul Istiq'faroh; Hitta Alfi Muhimmah (Jurnal Cakrawala Pendas, 2025)
Civics education in elementary schools often faces challenges due to conventional approaches that fail to optimally foster students' critical thinking skills. This study aims to identify and analyze the potential integration of Wordwall media, the Design Thinking approach, and local wisdom in enhancing critical thinking in Civics education. This research employs a Systematic Literature Review (SLR) method, reviewing articles published between 2015–2025 retrieved from databases such as Google Scholar, DOAJ, Scopus, and Garuda. Selected articles met the inclusion criteria and were analyzed using content analysis techniques to identify recurring themes, patterns, and research gaps. The findings show that Wordwall effectively improves concept comprehension and student engagement, Design Thinking fosters collaboration and problem-solving, while local wisdom strengthens the relevance of Pancasila values in students’ daily lives. However, very limited research integrates all three elements within the context of Civics education. This study recommends developing an innovative learning model that combines these approaches to meet the demands of the Merdeka Curriculum and shape students with critical, reflective, and value-oriented character traits. The results of this review serve as a conceptual foundation for educators and curriculum developers in designing more contextual and meaningful learning strategies.